Neural pathways for colorectal control, relevance to spinal cord injury and treatment: a narrative review. Issue 3 (March 2018) - Callaghan, Brid; Furness, John; Pustovit, Ruslan
Abstract Study design Narrative review. Objectives The purpose is to review the organisation of the nerve pathways that control defecation and to relate this knowledge to the deficits in colorectal function after SCI. Methods A literature review was conducted to identify salient features of defecation control pathways and the functional consequences of damage to these pathways in SCI. Results The control pathways for defecation have separate pontine centres under cortical control that influence defecation. The pontine centres connect, separately, with autonomic preganglionic neurons of the spinal defecation centres and somatic motor neurons of Onuf's nucleus in the sacral spinal cord. Organised propulsive motor patterns can be generated by stimulation of the spinal defecation centres. Activation of the somatic neurons contracts the external sphincter. The analysis aids in interpreting the consequences of SCI and predicts therapeutic strategies. Conclusions Analysis of the bowel control circuits identifies sites at which bowel function may be modulated after SCI. Colokinetic drugs that elicit propulsive contractions of the colorectum may provide valuable augmentation of non-pharmacological bowel management procedures.